2020
DOI: 10.1007/s12286-020-00465-2
|View full text |Cite|
|
Sign up to set email alerts
|

“For me democracy is …” meanings of democracy from a phenomenological perspective

Abstract: Meanings of democracy are far more complex than results of standardized survey research imply. They are diverse and intertwined with other individual concepts and subjective experiences. In terms of phenomenological adequacy, they are important first order constructions that can be used for building second order typologies and explanations for political action. Survey-based quantitative research has clear limits in terms of gathering such first order constructions, even if one wants to integrate them. Drawing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Measuring democracy, or more concretely, attitudes toward democracy, has a long tradition; however, what has been analyzed has changed more and more. Notably, the "meanings of democracy" approach to its measurement demands better measurement of the way democracy is perceived (Schedler and Sarsfield, 2007;Shin, 2017;Frankenberger and Buhr, 2020;Osterberg-Kaufmann et al, 2020;Quaranta, 2020;Davis et al, 2021). Amidst growing criticism, notably of the famous "satisfaction with democracy" question in international surveys (Canache et al, 2001;Shin, 2017), new measures are developed in an effort to differentiate between different understandings of democracy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Measuring democracy, or more concretely, attitudes toward democracy, has a long tradition; however, what has been analyzed has changed more and more. Notably, the "meanings of democracy" approach to its measurement demands better measurement of the way democracy is perceived (Schedler and Sarsfield, 2007;Shin, 2017;Frankenberger and Buhr, 2020;Osterberg-Kaufmann et al, 2020;Quaranta, 2020;Davis et al, 2021). Amidst growing criticism, notably of the famous "satisfaction with democracy" question in international surveys (Canache et al, 2001;Shin, 2017), new measures are developed in an effort to differentiate between different understandings of democracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, with respect to validity, it is essential not to include this question, except perhaps in interviews to begin the debate. It is definitely possible to ask questions about democracy's dimensions in interviews, as research has shown (Refle, 2019;Frankenberger and Buhr, 2020). However, this means that we descend at least one level and do not ask questions about democracy in general, but more concrete questions about minority rights, for example, to capture multiple dimensions.…”
Section: Multidimensionalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Second, all contributions deal with different aspects of the challenges mentioned above, as they discuss theoretical questions on conceptualization, expand knowledge about survey research by offering new theory-based conceptualizations based on new (Baniamin 2020) and existing (Wegscheider and Stark 2020) items. In addition to the use of qualitative interviews (Frankenberger and Buhr 2020), they introduce new methodological approaches from psychology (Osterberg-Kaufmann and Stadelmaier 2020) and linguistics (Dahlberg et al 2020) which underlines the importance of interdisciplinary research. The studies also vary according to regions (World: Wegscheider and Stark 2020; Europe: Dahlberg et al 2020;Frankenberger and Buhr 2020;Africa: Baniamin 2020;Asia: Osterberg-Kaufmann and Stadelmaier 2020) and different political levels (local level: Osterberg-Kaufmann and Stadelmaier 2020; regional level: Frankenberger and Buhr 2020;national level: Wegscheider and Stark 2020;Baniamin 2020;Dahlberg et al 2020).…”
Section: Contributions Of the Special Sectionmentioning
confidence: 99%